2017
DOI: 10.3390/ijerph14080854
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Human Placental Choriocarcinoma Cells with Formaldehyde and Benzene Induced Growth and Epithelial Mesenchymal Transition via Induction of an Antioxidant Effect

Abstract: Cigarette smoke (CS) causes about 480,000 deaths each year worldwide, and it is well-known to have harmful effects on the human body, leading to heart disease, stroke, lung cancer, and cardiovascular problems. In this study, the effects of formaldehyde (FA) and benzene (Bz), the main components of CS, on cell proliferation and epithelial mesenchymal transition (EMT) of JEG-3 human choriocarcinoma cells were examined to confirm the relationship between CS components and placenta carcinoma. Upon MTT assay, FA (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Since FA is a reactive chemical capable of forming many adverse side reactions in the cell, it is logical that the FA level must be strictly regulated. Interestingly, an increase of FA in certain types of cancer cells appears to be well tolerated 26,30,33,53,54 . To understand features of FA metabolism in normal cells, we probed the effect of increased levels of FA in primary human fibroblasts (FSK).…”
Section: Discussionmentioning
confidence: 99%
“…Since FA is a reactive chemical capable of forming many adverse side reactions in the cell, it is logical that the FA level must be strictly regulated. Interestingly, an increase of FA in certain types of cancer cells appears to be well tolerated 26,30,33,53,54 . To understand features of FA metabolism in normal cells, we probed the effect of increased levels of FA in primary human fibroblasts (FSK).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a series of studies have begun to explore the mechanism of FA-induced AD pathogenesis. As one of the markers of oxidative stress, the appearance of FA is often accompanied by an increase in ROS and lipid peroxides [ 5 , 9 , 10 , 11 ]. Strong oxidative stress and cytotoxicity can further lead to DNA lesions [ 12 ], endoplasmic reticulum stress (ERS) [ 11 ], and the impairment of mitochondrial function [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…As PPC is a rare disease, diagnosis before surgery is di cult [5]. The diagnostic criteria for PPC include a lack of a previous urological malignancy, solitary or predominant lung lesion without a primary gonadal site, elevated serum β-HCG levels that normalize following surgery or chemotherapy, and pathological con rmation of the disease [6].…”
Section: Discussionmentioning
confidence: 99%
“…The patient had a smoking history, which might be a risk factor for choriocarcinoma. It has been reported that formaldehyde and benzene, the main components of cigarette smoke, induce the growth and migration of human choriocarcinoma cells via regulation of the cell cycle and activation of oxidative stress [5]. However, research also showed that acrylonitrile, one of main components of cigarette smoke, has the potential to induce apoptosis of human choriocarcinoma cancer cells by activating ROS[6].…”
Section: Discussionmentioning
confidence: 99%